The collateral channel of open market operations - Nuno Cassola; François Koulischer (European Central Bank (ECB), 2016)
We build a model of collateral choice by banks that allows to recover the opportunity cost of collateral use and the access of banks to the interbank market. We estimate the model using country-level data on assets pledged to the European Central Bank from 2009 to 2011. The model can be used to quantify how changes in haircuts affect the collateral used by banks and can provide proxies for the funding cost of banks. Our results suggest for example that a 5% higher haircut on low rated collateral would have reduced the use of this collateral by 10% but would have increased the average funding cost spread between high yield and low yield countries by 5% over our sample period.
Keywords: E52; E58; G01; F36; 330; central bank; collateral; haircut; money market